KEMAMPUAN KEPEMIMPINAN PEMIMPIN PERBANKAN MENINGKATKANKAN MOTIVASI KERJA KARYAWAN RURAL BANK PADA BANK PERKREDITAN RAKYAT DI PROVINSI KALIMANTAN TIMUR - Agustinus Djiu (RJABM (Research Journal of Accounting and Business Management), 2017)
This research examines and analyzes: The influence of task Structure on work motivation. The influence Relationship consideration on work motivation. The influence task structure on Employee’s performance. The influence of Relationship consideration on Employee’s performance. The influence work motivation on employee’s performance.The population of study is all employees of Rural Bank Corporation and the samples are 135 employees, to whom the primary data have been collected by questionnaire. The answers of respondents through measuring indicators of each variable have been analyzed by using software program PLS (Partial Least Square).The result of statistical test and path analysis of the  hypothesis, have any conclusions as the findings of research : Task structure have influenced on Work motivation significantly with coefficient value 0.130 and Relationship consideration have also significant influence on work motivation with coefficient value 0.537. Task structure have significantly influenced on Performance with coefficient value 0.314.This findings justified the theoretical statements of some theorist and previous  empirical studies, that leadership style influenced motivation and Performance as had been introduced by Hersey-Blancard in Gibson (1995:553). Justified Motivation theory – Maslow’s hierarchy needs (1960’s), that employee has hierarchical needs of financial and non financial which will influence individual Motivation.The research is made as an empirical reference and for the useful practice, could be for developing Rural Bank East Kalimantan and for improving employee’s Motivation.